c-Fos expression in the hypothalamic paraventricular nucleus after a single treatment with a typical haloperidol and nine atypical antipsychotics: a pilot study - Kiss Alexander (Sciendo, 2018)
Objective. The aim of the present study was to find out whether acute effect of different doses of selected antipsychotics including aripiprazole (ARI), amisulpride (AMI), asenapine (ASE), haloperidol (HAL), clozapine (CLO), risperidone (RIS), quetiapine (QUE), olanzapine (OLA), ziprasidone (ZIP), and paliperidone (PAL) may have a stimulatory impact on the c-Fos expression in the hypothalamic paraventricular nucleus (PVN) neurons.